2005
DOI: 10.1038/sj.pcan.4500783
|View full text |Cite
|
Sign up to set email alerts
|

Putative role of serum insulin-like growth factor–1 (IGF-1) and IGF binding protein-3 (IGFBP-3) levels in the development of prostate cancer in Arab men

Abstract: Introduction: The incidence of clinical prostate cancer in the Arab population is among the lowest in the world. High serum IGF-1 level has been implicated as a possible risk factor for the development of prostate cancer in Caucasians. The purpose of this study was to determine serum IGF-1 and IGFBP-3 levels in healthy Arab men and in Arab men with newly diagnosed benign prostatic hyperplasia (BPH) and prostate cancer, and to compare these values with values reported in Caucasians. Patients and Methods: Subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…Epidemiological studies regarding the circulating IGFBP-3 concentration revealed both positive and inverse associations of IGFBP-3 with PCa [28,30,31,41]. Association between serum IGF-I, and ILGFBP levels with precancerous lesions of the prostate has also been reported.…”
Section: Variablesmentioning
confidence: 89%
See 1 more Smart Citation
“…Epidemiological studies regarding the circulating IGFBP-3 concentration revealed both positive and inverse associations of IGFBP-3 with PCa [28,30,31,41]. Association between serum IGF-I, and ILGFBP levels with precancerous lesions of the prostate has also been reported.…”
Section: Variablesmentioning
confidence: 89%
“…Evidence linking IGFBP-3 to PCa risk is inconsistent. The consequence of high circulating levels of IGFBP-3 on PCa risk in some studies is associated with increased PCa risk [28,29] whereas other studies report a protective role, concluding that high serum IGFBP-3 concentrations are associated with decreased cancer risk [30,31]. Additional studies report no association between IGFBP-3 concentrations and PCa [32,33].…”
Section: Introductionmentioning
confidence: 95%
“…The incidence of PCa in the Arab population is among the lowest in the world. Incidentally, one study has demonstrated that healthy Arab men have significantly lower serum IGF-I levels compared to healthy Caucasians [60].…”
Section: Population Studiesmentioning
confidence: 98%
“…[32] Previous study on Arab males indicated that IGF-1 and IGFBP-3 reached their peak levels during adolescence and gradually lowered with age. [33] IGFBP-3, the most prevalent form of the IGFBPs, has been linked with prostatic growth. About 75% of IGF-1 is bound to IGFBP-3, while 20-25% is bound to the other binding proteins (IGFBP-1, 2, 4 and 5), and less than 1% is carried in the unbound state in the circulation.…”
Section: Discussionmentioning
confidence: 99%